How Does AI Support Surgical Oncology? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming various medical fields, and surgical oncology is no exception. While still in its early stages, the inte...
Keywords: AI in Surgery and Robotics; Support; Surgical; Oncology; Artificial Intelligence; Machine Learning; Healthcare